2012
DOI: 10.1111/j.2041-1626.2012.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian undergraduate dental students' perceptions toward implant treatment and education

Abstract: Dental students of FD-UI are aware of implant treatment as a restorative option in replacing a single missing tooth. There is a need for a nationwide discussion for introducing a comprehensive implant dentistry curriculum in undergraduate dental education in Indonesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Ariani et al (35) Indonesia Study student survey Undergraduate students are aware of implant therapy as a restorative treatment option and plan to include implants in their future practice; nevertheless, they considered implant dentistry insufficiently covered in the current curriculum Moest et al (27) Germany Description programme I-lect â tutorial, providing practical experience in implant dentistry at an early stage of the curriculum, was positively perceived by the participating undergraduate students extractions (22), restoration of implants (16,22,23,28) or assisting in restorative procedures undertaken by residents or staff members (18,33). Actual placement of implants by students was only allowed in a limited number of programmes (21,22).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ariani et al (35) Indonesia Study student survey Undergraduate students are aware of implant therapy as a restorative treatment option and plan to include implants in their future practice; nevertheless, they considered implant dentistry insufficiently covered in the current curriculum Moest et al (27) Germany Description programme I-lect â tutorial, providing practical experience in implant dentistry at an early stage of the curriculum, was positively perceived by the participating undergraduate students extractions (22), restoration of implants (16,22,23,28) or assisting in restorative procedures undertaken by residents or staff members (18,33). Actual placement of implants by students was only allowed in a limited number of programmes (21,22).…”
Section: Resultsmentioning
confidence: 99%
“…In general, two types of publications about undergraduate implant education could be identified: first, those dealing with a single programme and second, descriptive studies including multiple programmes . A common trend in the last decades is a steady increase in undergraduate schools, offering some kind of implant‐related education up to the point that at present around 100% of the programmes included the scientific basis for implant dentistry in their curriculum .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous articles regarding awareness about dental implants among the general public but few articles were found to assess the awareness in the dental profession. [5][6][7][8] Many surveys have shown that the primary source of patient information on dental implants are dentists. 9,10 Awareness about dental implants is increasing among general public and greater number of people are seeking information about it.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, during the clinical years, students are qualified to diagnose and treat oral medicine patients if they have individually performed full examinations of at least four oral medicine patients with a passing grade under individual supervision from the academic staff in the Department of Oral Medicine [27].…”
Section: Introductionmentioning
confidence: 99%